Transthoracic Vertebral Distraction and Stabilization in 10 Dogs with Congenital Thoracic Vertebral Malformations - Farré Mariné, Alba; De Risio, Luisa; Mascort, Joan; Jiménez Peláez, Manuel; López, Marta; Stabile, Fabio; Luján Feliu-Pascual, Alejandro (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to describe the surgical technique and outcomes of dogs with congenital thoracic vertebral body malformations (CTVBM) treated with unilateral vertebral distraction and stabilization with monocortical screws and polymethylmethacrylate (PMMA).Study Design Medical records of 10 client-owned dogs with CTVBM were retrospectively searched for signalment, history, neurological examination, neurological grade based on the modified Frankel scale (MFS), diagnostic method, CTVBM location, Cobb's angle, and vertebral canal angle (VCA), surgical procedure, complications and long-term follow-up.Results One dog suffered cardiac arrest 24 hours post-surgery and died. Median follow-up in nine dogs was 26.5 months (12–50 months). Cobb's angle improved from 33–83 to 10–46 degrees and the VCA ratio from 97–138 to 122–164 degrees. The MFS improved from 3 (n = 3)–4 (n = 7) to 4 (n = 2)–6 (n = 7). Seven dogs recovered full function. Nine dogs improved after surgery compared with preoperative status, recovering ambulation when lost or achieving normal neurological examination in seven cases. No complications were reported during the follow-up period (12–50 months).Conclusion Unilateral transthoracic vertebral distraction and stabilization with monocortical screws and PMMA for treatment of compressive myelopathy due to CTVBM achieved long-term neurological improvement in 9 of 10 dogs.
Keywords: congenital vertebral body malformation; transthoracic; stabilization; distraction; dog